UJI TIGA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium cepa, L.) - Ester N. Pajow; Joko Purbopuspito; Meldi T.M. Sinolungan (Universitas Sam Ratulangi, 2018)
Abstract Shallots are an important vegetable commodity in North Sulawesi with a high market demand. This research tested the type of manures for the growth and production of shallot plants using a field experiment at the BPTP SULUT Experimental Field and soil testing at the Soil Fertility Laboratory, Faculty of Agriculture, UNSRAT. The field experiment used four types of manure treatments in six replications, so that 24 experimental beds were obtained. From this study, the best type of manure for plant growth, increasing the number of leaves and the number of tillers, and for the production of fresh shallots is obtained by dose of a 40 tons of chicken manure /ha or a 40 tons of cow manure /ha in contrast to a 40 tons of pig manure /ha or a control without manure, which is gained from soil fertility conditions with 1.62-1.70% C-organic; soil pH 6.60-6.64; 0,137-0,148% soil N-total land; 18.28-21.05 ppm soil P-available; and 20.44-23.54 ppm soil Kavailable. Keywords : chicken manure, cow manure, shallots.